2011
DOI: 10.1186/1748-717x-6-80
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes in patients with stage III versus limited stage IV non-small cell lung cancer

Abstract: BackgroundStandard therapy for metastatic non small cell lung cancer (NSCLC) includes palliative systemic chemotherapy and/or radiotherapy. Recent studies of patients with limited metastases treated with curative-intent stereotactic body radiation therapy (SBRT) have shown encouraging survival. We hypothesized that patients treated with SBRT for limited metastases have comparable outcomes with those treated with curative-intent radiation for Stage III NSCLC.MethodsWe retrospectively reviewed the records of NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 26 publications
(27 reference statements)
5
54
0
1
Order By: Relevance
“…e 7th AJCC Staging system was used to categorize patients and two groups of patients were used in this study: stage III NSCLC and stage IV NSCLC. Among patients with Stage III NSCLC, metastatic recurrence was characterized as limited metastatic or extensive metastatic disease as described in a previous report [15]. All patients were assessed with diagnostic CT or PET/CT imaging to identify metastatic lesions.…”
Section: Patientsmentioning
confidence: 99%
“…e 7th AJCC Staging system was used to categorize patients and two groups of patients were used in this study: stage III NSCLC and stage IV NSCLC. Among patients with Stage III NSCLC, metastatic recurrence was characterized as limited metastatic or extensive metastatic disease as described in a previous report [15]. All patients were assessed with diagnostic CT or PET/CT imaging to identify metastatic lesions.…”
Section: Patientsmentioning
confidence: 99%
“…This is a more difficult question to answer at this time, but from several retrospective and single institution studies, it is apparent that local treatment could add survival value in this patient population [40,41,44,[46][47][48]. Part of the reason for the difficulty in identifying if a limited metastatic disease state exists in NSCLC is that traditional systemic therapy trials for stage IV NSCLC did not provide details of number of disease sites as long as there was disease that was measurable for treatment response.…”
Section: Considerations Regarding Use Of Sabr In Metastatic Nsclcmentioning
confidence: 94%
“…According to our recently completed phase II study, there are indeed patients with limited sites of metastatic disease who can have significant PFS and OS when treated aggressively locally in comparison to historical values [45]. Multiple retrospective studies have demonstrated significant PFS times when oligometastatic disease of multiple pathologies, including NSCLC, was treated with radiation [40,41,44,[46][47][48]. Our recommendations would be to use SABR in the second or beyond line setting in patients with limited metastatic disease who have progressed in less than or equal to 6 sites (including primary disease location) after systemic therapy based on our published phase II experience [45].…”
Section: Considerations Regarding Use Of Sabr In Metastatic Nsclcmentioning
confidence: 98%
“…Dans cette étude, il existait un avantage de survie chez les malades ayant présenté une réponse complète à la chimiothé-rapie initiale [14]. D'autres études, le plus souvent rétrospectives ont rapporté une efficacité chez des patients répondeurs à la chimiothé-rapie initiale et présentant un nombre peu important de métastases [5,10,24]. Dans tous les cas les doses de radiothérapies étaient supérieures à 30 Gy.…”
Section: Thérapies Moléculaires Cibléesunclassified